ARE WE DISCUSSING SUDEP? A RETROSPECTIVE CASE NOTE ANALYSIS. (29th November 2012) - Waddell, B; McColl, K; Turner, C; Norman, A; Coker, A; White, K; Roberts, R; Heath, CA
Abstract : Background: Sudden unexplained death in epilepsy (SUDEP) is uncommon. Discussing the risk of SUDEP can be difficult, particularly in those where the risk is considered low, and previous studies have suggested that clinical practice varies widely. The Scottish Intercollegiate Guidelines Network (SIGN) suggest information on SUDEP is 'essential' and National Institute of Clinical Excellence (NICE) recommend that 'tailored information on the person's relative risk of SUDEP should be part of the counselling process…'. Aim: To evaluate if discussion of SUDEP risk is being documented in clinical records. Methods: A retrospective case note review was undertaken in those with an established diagnosis of epilepsy attending clinic between 1 January 2009 and 30 June 2009. Results: Overall, a documented SUDEP discussion was noted in 14/345 (4%) cases. Analysis failed to demonstrate a statistically significant association between the identification of a documented SUDEP discussion and a number of risk factors including: gender; proposed non-compliance; learning disability; drug-resistance; frequency of generalised tonic-clonic seizures; age at onset; seizures for ≥15 years. Conclusion: There is no documented evidence from this retrospective case note analysis to suggest that clinicians are discussing SUDEP in the majority of cases.